Quantitative breast density analysis using tomosynthesis and comparison with MRI and digital mammography. (February 2018) - Moon, Woo Kyung; Chang, Jie-Fan; Lo, Chung-Ming; Chang, Jung Min; Lee, Su Hyun; Shin, Sung Ui; Huang, Chiun-Sheng; Chang, Ruey-Feng
Highlights: We proposed a quantitative method to estimate breast density and compared tomosynthesis with MRI and digital mammography. An automatic skin removal was adopted and a FCM classifier was used to separate the fibroglandular tissues from breast area. There were significant correlations between tomosynthesis with MRI and with digital mammography values < . Tomosynthesis could provide useful 3-D information on breast density through proposed method. We discovered and solved the problem of the different expression of aggregated fibroglandular tissue in different modalities. Abstract: Background and Objective: Breast density at mammography has been used as markers of breast cancer risk. However, newly introduced tomosynthesis and computer-aided quantitative method could provide more reliable breast density evaluation. Methods: In the experiment, 98 tomosynthesis image volumes were obtained from 98 women. For each case, an automatic skin removal was used and followed by a fuzzy c-mean (FCM) classifier which separated the fibroglandular tissues from other tissues in breast area. Finally, percent of breast density and breast volume were calculated and the results were compared with MRI. In addition, the percent of breast density and breast area of digital mammography calculated using the software Cumulus (University of Toronto, Toronto, ON, Canada.) were also compared with 3-D modalities. Results: Percent of breast density and breast volume, which were computed from tomosynthesis, MRI and digital mammography were 17.37% ± 4.39% and 607.12 cm 3 ± 323.01 cm 3, 20.3% ± 8.6% and 537.59 cm 3 ± 287.74 cm 3, and 12.03% ± 4.08%, respectively. There were significant correlations on breast density as well as volume between tomosynthesis and MRI ( R = 0.482 and R = 0.805), tomosynthesis and breast density with breast area of digital mammography ( R = 0.789 and R = 0.877), and MRI and breast density with breast area of digital mammography ( R = 0.482 and R = 0.857) (all P values < .001). Conclusions: Breast density and breast volume evaluated from tomosynthesis, MRI and breast density and breast area of digital mammographic images have significant correlations and indicate that tomosynthesis could provide useful 3-D information on breast density through proposed method.